Religious Education and Personal Mentality; As A Practical Existence of Students - Abdullah B (Journal of Research and Multidisciplinary, 2020)
Religiosity and education are very important in the success of national education targets in Indonesia based on this matter, and religious education provides knowledge. It shapes the attitudes, personalities, and skills of students in practicing their spiritual teachings, which is carried out at least through subjects/lectures on all lines, levels, and types of education. At the same time, religiosity education also prepares students can play a role in mastery of this knowledge of religious teachings or becomes an expert in spiritual experience and practice to the teachings of his religion." Written in government regulation No. 55 of 2007, especially for Indonesian people who have faith and are devoted to God Almighty and have a good character, can maintain peace and harmony between religious and inter-religious relations. While religious education prepares students to become members of the community who understand and practice the values ​​of their spiritual teachings and become experts in religious knowledge.